2006
DOI: 10.1007/s00127-005-0018-y
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of mental health screening and intervention in the HUNT population study

Abstract: Though attitude towards psychiatry among GPs and participants was generally positive, response to the IDANT study was inadequate. Relatively few new cases were detected, yet the results indicate that the GPs altered their psychiatric care and practice markedly within the PHRG. Whether the educational programme had an impact on psychiatric services in the county in general cannot be answered in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Other studies on health check participants have found similar associations with mental distress: female gender ( Bjerkeset et al, 2006 , Crisp and Priest, 1971 , Hildrum et al, 2007 , Gil et al, 2006 , Jørgensen et al, 2009 ), low education ( Bjerkeset et al, 2006 , Hildrum et al, 2007 , Gil et al, 2006 , Jørgensen et al, 2009 ), unemployment ( Bjerkeset et al, 2006 , Jørgensen et al, 2009 ), risky health behaviour ( Pisinger et al, 2009 , Bjerkeset et al, 2006 , Hildrum et al, 2007 ), and high risk for development of ischemic heart disease ( Jørgensen et al, 2009 ). Although the age groups and the tools for assessing MH in these studies differed from the ones in Check Your Health , the results support our findings: Poor MH found in health check participants is associated with disadvantaged socioeconomy, health behaviour, and high risk of CVD.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Other studies on health check participants have found similar associations with mental distress: female gender ( Bjerkeset et al, 2006 , Crisp and Priest, 1971 , Hildrum et al, 2007 , Gil et al, 2006 , Jørgensen et al, 2009 ), low education ( Bjerkeset et al, 2006 , Hildrum et al, 2007 , Gil et al, 2006 , Jørgensen et al, 2009 ), unemployment ( Bjerkeset et al, 2006 , Jørgensen et al, 2009 ), risky health behaviour ( Pisinger et al, 2009 , Bjerkeset et al, 2006 , Hildrum et al, 2007 ), and high risk for development of ischemic heart disease ( Jørgensen et al, 2009 ). Although the age groups and the tools for assessing MH in these studies differed from the ones in Check Your Health , the results support our findings: Poor MH found in health check participants is associated with disadvantaged socioeconomy, health behaviour, and high risk of CVD.…”
Section: Discussionmentioning
confidence: 71%
“…To our knowledge, only few other studies have included MH as a part of the risk assessment in a health check of the general population ( Bjerkeset et al, 2006 , Crisp and Priest, 1971 ). However, some studies have reported MH status in the baseline characteristics of participants in health checks of the general population ( Hildrum et al, 2007 , Chang et al, 2013 , Gil et al, 2006 , Jørgensen et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was divided into two subscales, HADS-A (anxiety) and HADS-D (depression) according to previous studies 20 21. Both scores for depression and anxiety were recoded into low, 0 (rating 0–7), and high, 1 (rating 8–42).…”
Section: Methodsmentioning
confidence: 99%
“…In case of an extremely high HADS score (HADS total score ≥ 25) both the participant and his GP got a warning note approximately 6 weeks after the HUNT-2 examination, in the same way as they got for somatic risk factors like high cholesterol. Details on the IDANT study have been published elsewhere ( 7 ).…”
Section: Inception Of the Spifamentioning
confidence: 99%